Pre-operative cognitive training to prevent postoperative cognitive dysfunction in older patients cognitrain: A randomised controlled trial / Ivy Sim Chui Geok - Ivy Sim , Chui Geok (2018)
The incidence of post-operative cognitive dysfunction in the elderly is increased and the subsequent impact can be devastating as patients need to retain their faculties in order to remain independent. A pilot study was carried out to determine the effectiveness of a novel home-based cognitive training on the incidence of delirium and post-operative cognitive dysfunction in patients aged 65 and above undergoing elective surgery. 18 subjects were recruited in pre-operative anaesthetic clinic and randomised into 2 groups. The intervention group was taught to perform cognitive training at home. Pre-operative and post-operative cognitive assessments were carried out and results compared. No patients developed delirium post-operatively. There was a low compliance rate (50%) among subjects leading to mixed findings on cognitive testing.